2022
DOI: 10.1002/biot.202100328
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid fortification of zucchini fruits using a viral RNA vector

Abstract: Background Carotenoids are health‐promoting metabolites in livestock and human diets. Some important crops have been genetically modified to increase their content. Although the usefulness of transgenic plants to alleviate nutritional deficiencies is obvious, their social acceptance has been controversial. Results Here, we demonstrate an alternative biotechnological strategy for carotenoid fortification of edible fruits in which no transgenic DNA is involved. A viral RNA vector derived from zucchini yellow mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In particular, surprisingly little is known on the factors involved in natural differentiation of chloroplasts into chromoplasts (Sadali et al, 2019; Torres-Montilla and Rodriguez-Concepcion, 2021). We have recently demonstrated that chromoplasts harboring high levels of endogenous carotenoids can be synthetically created in leaves and other chloroplast-harboring organs of any plant species by overexpressing the Pantoea ananatis crtB gene, encoding a bacterial phytoene synthase (Houhou et al, 2022; Llorente et al, 2020). Plastid targeting of either the unmodified crtB protein (by means of a cryptic plastid targeting sequence present in the protein) or of a modified version with a plant plastid targeting sequence fused to its N-terminus (referred to as (p)crtB) resulted in a dramatic production of phytoene, the first committed intermediate of the carotenoid pathway (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, surprisingly little is known on the factors involved in natural differentiation of chloroplasts into chromoplasts (Sadali et al, 2019; Torres-Montilla and Rodriguez-Concepcion, 2021). We have recently demonstrated that chromoplasts harboring high levels of endogenous carotenoids can be synthetically created in leaves and other chloroplast-harboring organs of any plant species by overexpressing the Pantoea ananatis crtB gene, encoding a bacterial phytoene synthase (Houhou et al, 2022; Llorente et al, 2020). Plastid targeting of either the unmodified crtB protein (by means of a cryptic plastid targeting sequence present in the protein) or of a modified version with a plant plastid targeting sequence fused to its N-terminus (referred to as (p)crtB) resulted in a dramatic production of phytoene, the first committed intermediate of the carotenoid pathway (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…ZYMV is an important pathogen of cucurbits that reduces yields in some of the most important crops worldwide, such as squash, melon or cucumbers ( Gal-On, 2007 ; Simmons et al, 2013 ). So far, ZYMV has been used in biotechnology to produce antiviral and antitumor proteins or metabolites ( Arazi et al, 2001b ; Arazi et al, 2002 ; Cordero et al, 2017 ; Majer et al, 2017 ), or to fortify zucchini fruits with carotenoids ( Houhou et al, 2022 ). Furthermore, zucchini plants may be suitable biofactories due to their rapid growth rate and capacity for high biomass production over a short period of time, thereby facilitating production of a high amount of the desired product.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the use of potyviral vectors for expressing heterologous proteins in plants, and even an entire biosynthetic pathway ( Bedoya et al, 2010 ; Bedoya et al, 2012 ; Majer et al, 2015 ; Majer et al, 2017 ; Cordero et al, 2018 ; Martí et al, 2020 ; Houhou et al, 2022 ). In this study, we report the production of genetically encoded viral nanoparticles derived from ZYMV and TEV as nanoscaffolds for nanobody presentation.…”
Section: Introductionmentioning
confidence: 99%
“…ZYMV is an important pathogen of cucurbits that reduces yields in some of the most important crops worldwide, such as squash, melon, or cucumbers (Gal-On, 2007;Simmons et al, 2013). So far, ZYMV has been used in biotechnology to produce antiviral and antitumor proteins or metabolites (Arazi et al, , 2002, or to fortify zucchini fruits with carotenoids (Houhou et al, 2022). Furthermore, zucchini plants may be suitable biofactories due to their rapid growth rate and capacity for high biomass production over a short period of time, thereby facilitating production of a high amount of the desired product.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the use of potyviral vectors for expressing heterologous proteins in plants, and even an entire biosynthetic pathway Cordero et al, 2018;Houhou et al, 2022). In this study, we report the production of genetically encoded viral nanoparticles derived from ZYMV and TEV as nanoscaffolds for nanobody presentation.…”
Section: Introductionmentioning
confidence: 97%